Alamat ng duhat = The legend of the Java plum - Matias, Segundo D.; Salegumba, Rovi Jesher R. ([Quezon City] : Lampara Publishing House, 2012)
"Once upon a time, in the mountainous region of a certain province, there was a tribe that lived in the center of a vast forest--the Atas. Into this dark-skinned tribe Duha was born with a fair complexion. In the city Duha met a young man who brought her untold sadness, reason for her to implore the King Sun to make her as dark as her tribe. Since then, she spent her whole life in the service of her tribe. Find out in this modern legend why the Java plum has a black skin but with a white flesh as pure as Duha's heart."
Don Carlos Palanca Memorial Awards for Literature, Unang Gantimpala, Maikling Kathang Pambata, 2011
Keywords: Children's stories, Filipino; Race relations -- Fiction -- Juvenile literature; Ethnic groups -- Fiction -- Juvenile literature